Une étude cristallographique: superspace description of a commensurate composite cocrystal of 4, 4′-dinitrobiphenyl and biphenyl. Issue 3 (13th December 2021) - Rekis, Toms; Ramakrishnan, Sitaram; Kotla, Surya Rohith; Bao, Jin-Ke; Eisele, Claudio; Schönleber, Andreas; Noohinejad, Leila; Paulmann, Carsten; Tolkiehn, Martin; van Smaalen, Sander
Abstract : The structure of a 4, 4′-dinitrobiphenyl and biphenyl 3 : 1 composite cocrystal is presented in (3 + 1)D superspace. Abstract : We report the structure of a 3 : 1 cocrystal of 4, 4′-dinitrobiphenyl and biphenyl. The cocrystal can be regarded as a commensurate column composite crystal and therefore is described in superspace. The structure is monoclinic at 100 K (superspace group C 2( σ 1 0 σ 3 )0), but undergoes a single-crystal-to-single-crystal phase transition upon cooling, which results in a triclinic distortion at 20 K ( C 1( σ 1 σ 2 σ 3 )0). Unlike similar symmetry-lowering phase transitions, this transition is not found to induce twinning. Other structurally similar cocrystals with 4, 4′-dinitrobiphenyl and small organic molecules have been reported in the literature demonstrating that 4, 4′-dinitrobiphenyl is prone to form composite crystals.